Влияние окружной неравномерности свойств материала на неосесимметричное деформирование ротора турбины - Шульженко, Н. Г.; Гонтаровский, П. П.; Протасова, Т. В. (НТУ "ХПИ", 2014)
Оценена возможность необратимого деформирования роторов вследствие окружной неравномерности предела текучести. Численные исследования выполнены на основе метода конечных элементов в сочетании с разложением решений в окружном направлении в ряды Фурье. Показано, что с превышением номинальной частоты вращения появляющиеся местные пластические деформации вызывают значительный прогиб ротора при окружной неравномерности предела текучести материала.

The consideration was given to the irreversible deformation of steam turbine rotors caused by the circumferential inhomogeneity of material properties, based on the numerical analysis of their three-dimensional mode of deformation. To analyze asymmetric mode of deformation of the elements and units of power machines in the form of rotary bodies we developed the technique based on the use of semianalytical method of finite elements. The meridian section of the structure is split into finite elements and in the circumferential direction the solution is described by Fourier series. The ductility strain, anisotropy and a change in material characteristics in the circumferential direction have been taken into consideration. The rotor flexures at the circumferential inhomogeneity of yield point have been determined. It has been shown that as the nominal rotation frequency is exceeded originating local ductility strains result in the considerable rotor flexure, which produces negative influence on the operation reliability of the turbine unit.
The influence of the circumferential inhomogeneity of material properties on the asymmetric deformation of the turbine rotor
Keywords: прогиб ротора; метод; ротор паровой турбины; steam turbine rotor; asymmetric deformation; rotor flexure; semianalytical method of finite elements